Eco-Test at Vehicle Testing Centres - Štrumberger, Nada; Kovačić, Zoran; Gospočić, Alen (Promet - Traffic&Transportation, 2003)
Following the world conference on sustainable developmentof ecology, the care for the environment has to be strictlycomplied with, and this should be the task both of every individualand of the society as an organised whole. The work presentsconcrete measurements from practice and the indicators of thesituation regarding motor vehicles in Croatia. The EGO-TESThas been performed in Croatia according to the European Uniondirectives; first on the vehicles with petrol engines. Now, it isstarting to be applied on the vehicles with Diesel engines as well.Compliance with the EGO TEST regarding motor vehicles inCroatia will take into consideration the guidelines provided bythe European Union and thus reduce the harm from exhaustgases and noise pollution, and increase the possibility of usingmotor vehicles in order to reduce the danger and increase thesafety on the roads by excluding old vehicles from traffic.